The factors mediating change in people practising mindfulness - Watkin, Matthew (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
This study examines the experience of people who have begun practising mindfulness as it is taught in the Mindfulness-Based Stress Reduction programme (MBSR). The study has two aims: 1) to conceptualise the psychological mechanisms underpinning any change, and 2) to see if the changes produced are the same or similar to those produced in a cognitive therapy programme. The study focuses on two female participants, both with diagnosable psychopathology, who were part of the same MBSR programme at the Cape Town Medi-Clinic. Quantitative self-report measures of depression, anxiety, and medical symptoms were used as a measure of change. In-depth qualitative data which explored psychological, emotional and behavioural changes came from semi-structured interviews taken before, during, and immediately after the MBSR, and at a one-month follow-up. The interview data was supplemented by daily diaries documenting the participants' experiences of mindfulness, together with in-session video recordings. The analysis of these cases provide support for the model proposed by Segal, Teasdale and Williams (2002) of the factors underpinning improvement using mindfulness as a treatment. The changes were found to be similar, but not identical, to those that one would expect in a cognitive therapy programme.
Keywords: Cognitive therapy; Meditation; Depression, Mental; Anxiety -- Psychological aspects